Enhancing workers safety in worksites through augmented GNSS sensors. (March 2018) - D'Arco, Mauro; Renga, Alfredo; Ceccarelli, Andrea; Brancati, Francesco; Bondavalli, Andrea
Highlights: A GNSS-augmentation approach to localize workers in worksites is proposed. Required facilities consist in smart human-assistive wearable devices. Devices combine relative distance measurements and GPS data. No ground infrastructures are necessary to system operation. Fast set-up and dismantle times of the worksite are granted. Abstract: Human-assistive wearable technologies can monitor the position of a worker in a critical worksite and improve his safety by raising warnings when he is in a dangerous zone. In railway worksites, it is observed that GNSS localization is not applicable due to the relevant localization errors, which are only partially attributable to the specific characteristics of the worksite. Besides, alternative solutions that rely on the support of anchors have the drawback of lengthening the set-up and dismantle time of the worksite. To provide safe localization of railway trackside workers, a system that exploits augmented-GNSS wearable sensors is proposed. Each sensor includes a GPS receiver capable of sharing its coordinates with the other sensors, and is further complemented with a low-cost multi-way distance meter to measure its distance from the other sensors. The main attention is paid to the data fusion approach adopted to improve the accuracy of the position estimate by combining the relative distance measurements to the GPS coordinates.